Comparison of chemical composition of enamel and dentine in human, bovine, porcine and ovine teeth - Teruel, Juan de Dios; Alcolea, Alberto; Hernández, Ana; Ruiz, Antonio José Ortiz (Archives of oral biology, 2015)
•Chemical composition of human, bovine, porcine and ovine teeth has been studied.•C/N analysis showed that bovine dentine and enamel are the most similar to the human ones.•TG–MS showed large differences between human and bovine, ovine and porcine enamel.•Human enamel and dentine contained a higher Ca/P ratio than the animal species.•Human enamel and dentine contained lower quantities of Mg, S, Zn than the animal ones. The aim of this paper was to compare the chemical composition of human teeth with other mammal species that are likely candidates for replacing them in studies that test dental material. Dentine and enamel fragments extracted from 400 sound human, bovine, porcine and ovine – 100 teeth per species – incisors and molars were mechanically ground up to a final particle size of less than 100μm. C/N analysis, thermogravimetric analysis coupled to mass spectrometry (TG–MS), and wavelength dispersive X-ray fluorescence (WDXRF) were used to analyse the samples’ composition. Elemental analysis showed more organic carbon and nitrogen in dentine than in enamel. Human enamel was the most highly mineralised, with C and N values close to hydroxyapatite. Bovine dentine and enamel were the most similar to human. TG–MS: in all species, enamel contained less carbon and organic matter than dentine. Thermal decomposition of human enamel showed great similarity to synthetic hydroxyapatite, and large differences from bovine, ovine and porcine enamel. Thermal decomposition showed the greatest similarity between human and bovine dentine. WDXRF: Dentine contained larger quantities of Mg, S, Sr and Zn than enamel. Enamel contained larger quantities of P, Ca, Cl, Cu, K and Ca/P ratio than dentine. Human enamel and dentine contained a higher Ca/P ratio, larger quantities of Cl and Cu and lower quantities of Mg, S, Zn than the animal species. Elemental analysis, TG–MS and WDXRF have shown that human and bovine enamel and dentine show the greatest similarity among the species analysed.